1973
DOI: 10.1128/aac.4.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin of a Group A Streptococcus: Partial Purification and Properties

Abstract: The production of bacteriocin-like inhibition by certain strains of group A streptococci was demonstrated during the growth of these organisms on solid nutrient media. Active bacteriocin could not be recovered from broth cultures, possibly because of its inactivation by streptococcal proteinase. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 25 publications
(18 reference statements)
1
55
0
Order By: Relevance
“…However, some "auto-inhibitory" activity was observed when high-titre extracts were tested, indicating that the immunity was not complete. Immunity breakdown in bacteria exposed to high concentrations of homologous bacteriocine is commonly observed in grampositive species including streptococci (Tagg et al, 1973b;Tagg, Dajani and Wannamaker, 1975). However, inhibitor-negative derivatives of the M4T4 strains were more sensitive to the specific inhibitor than the parent strain; this suggests a possible plasmid-type linkage between the genes for production and those for immunity similar to that reported for streptococcin A-FF22 (Tagg and Wannamaker, 1976).…”
Section: Discussionmentioning
confidence: 62%
“…However, some "auto-inhibitory" activity was observed when high-titre extracts were tested, indicating that the immunity was not complete. Immunity breakdown in bacteria exposed to high concentrations of homologous bacteriocine is commonly observed in grampositive species including streptococci (Tagg et al, 1973b;Tagg, Dajani and Wannamaker, 1975). However, inhibitor-negative derivatives of the M4T4 strains were more sensitive to the specific inhibitor than the parent strain; this suggests a possible plasmid-type linkage between the genes for production and those for immunity similar to that reported for streptococcin A-FF22 (Tagg and Wannamaker, 1976).…”
Section: Discussionmentioning
confidence: 62%
“…Production of inhibitors by strains P2 and P9 was nevertheless somewhat reduced by incubation at a more neutral pH. Previous studies (Tagg et al, 1973a) indicated that the production of streptococcin A-FF22 in solid medium by strain P2 was enhanced at lower p H .…”
Section: Discussionmentioning
confidence: 88%
“…The production of bacteriocine-like substances by streptococci of several Lancefield groups has been described: group A (Sherwood et al, 1949;Kuttner, 1966;Overturf and Mortimer, 1970;Kolesnichenko and Totolyan, 197 1;Prakash, Ravindran and Sharma, 1973;Tagg, Read and McGiven, 1973a); group B (Kuttner, 1966;Kramer and Brandis, 1972;Prakash et al, 1973;Tzannetis, Poulaki-Tsontou and Papavassiliou, 1974;Tagg, Dajani and Wannamaker, 1975); and group D (Brock, Peacher and Pierson, 1963;Tzannetis, Leonardopoulos and Papavassiliou, 1970;Kekessy and Piguet, 1971;PleceaS, Bogdan and Vereanu, 1972). Typing schemes have been established for the differentiation of group-D streptococci on the basis of their production of (Tzannetis et al, 1970) and sensitivity to (PleceaS et al, 1972) bacteriocine-like substances or both (Kekessy and Piguet, 1971).…”
mentioning
confidence: 99%
“…Sterilized water (2 ml) was supplemented to control tubes when determining growth in the absence of inhibitor. Inhibitory activity was also measured using a plate assay, modified from that of Tagg et al (1973). A lawn of indicator strain was first seeded by mixing 0n2 ml of an overnight culture with 15n5 ml melted (" 45 mC) solid medium [MDM supplemented with (l − ") : 10 g agar, 2 g Trypticase, 1 g yeast extract, 0n25 g each of cysteine/HCl and Na # S.9H # O].…”
Section: Methodsmentioning
confidence: 99%